The existence of positive periodic solutions of a generalized - Meili Li; Maoan Han; Chunhai Kou (Mathematical Biosciences and Engineering)
In this paper, the existence of positive periodic solutions of aclass of periodic $n$-species Gilpin-Ayala impulsive competitionsystems is studied. By using the continuation theorem ofcoincidence degree theory, a set of easily verifiable sufficientconditions is obtained. Our results are general enough to includesome known results in this area.